Late urological manifestation of stress incontinence surgery. Issue 5 (21st May 2021) - Salfity, Louay; Dekel, Etay; Sahai, Arun; Faure Walker, Nicholas
Abstract : The Stamey procedure was a popular procedure for female stress incontinence practiced widely in the 1980s before it was abandoned owing to high complication rates. The procedure aimed to suspend the bladder neck by placing two transvaginal Dacron buttress grafts either side of the bladder neck and suspending them with sutures passed through the retropubic space and tied suprapubically. Erosion of the graft into the bladder was a recognised complication. We report a case of an 84-year-old lady who presented with urinary symptoms forty years after an unspecified stress incontinence procedure. Imaging and cystoscopy revealed an eroded graft in her bladder wall. Further investigation revealed the graft was a Dacron buttress from a Stamey procedure. This case highlights the importance of having a working knowledge of historical techniques that may present with complications many years later and recognising the symptoms that should prompt early investigation.